Pengaruh Keagamaan Pada Remaja - Setiawan dkk., Edi; Asna, Atikah (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
Adolescence is a crucial transition period in individual religious development. This research examines how physical, psychological, and social factors influence the development of teenagers’ religious spirit. The study identifies three phases of development: early (12-15 years), intermediate (15-18 years), and late (18-21 years). In each phase, teenagers experience growth in critical thinking, social emotions, and moral considerations that are significantly influenced by their environment. The results indicate that education and social context play a vital role in shaping teenagers’ religious attitudes, manifesting both positively and negatively.